A 100 kHz Time-Resolved Multiple-Probe Femtosecond to Second Infrared Absorption Spectrometer. Issue 4 (April 2016) - Greetham, Gregory M.; Donaldson, Paul M.; Nation, Charlie; Sazanovich, Igor V.; Clark, Ian P.; Shaw, Daniel J.; Parker, Anthony W.; Towrie, Michael
We present a dual-amplifier laser system for time-resolved multiple-probe infrared (IR) spectroscopy based on the ytterbium potassium gadolinium tungstate (Yb:KGW) laser medium. Comparisons are made between the ytterbium-based technology and titanium sapphire laser systems for time-resolved IR spectroscopy measurements. The 100 kHz probing system provides new capability in time-resolved multiple-probe experiments, as more information is obtained from samples in a single experiment through multiple-probing. This method uses the high repetition-rate probe pulses to repeatedly measure spectra at 10 µs intervals following excitation allowing extended timescales to be measured routinely along with ultrafast data. Results are presented showing the measurement of molecular dynamics over >10 orders of magnitude in timescale, out to 20 ms, with an experimental time response of <200 fs. The power of multiple-probing is explored through principal component analysis of repeating probe measurements as a novel method for removing noise and measurement artifacts.